REFORMASI PENEGAKAN HUKUM KEKERASAN SEKSUAL TERHADAP ANAK SEBAGAI SALAH SATU BENTUK PERLINDUNGAN ANAK YANG BERKELANJUTAN - Arliman, Laurensius (Justitia Jurnal Ilmu Hukum, 2023)
Abstract : Child protection as one of the guarantees of human rights is evident from its form regeneration development of a country. It is very unfortunate when children are sexually assaulted during their childhood. Their future ruined, because there are psychological and mental trauma. In restructuring the protection of children from the dangers of sexual violence will require reform of law enforcement to the threat of sexual violence. The pattern of structuring reform of law enforcement on an ongoing child protection must be implemented. In order for this republic created a generation who can be relied on to ensure the survival and progress of this country.